Attentional focus in team sports: Effects of an intervention program on football players - Tassi, J. M.; Fajardo, M. A. L.; Garcia, J. D.; Calvo, T. G.; Ponce, I. G. (European Journal of Human Movement, 2023)
The cognitive processes that influence athletic performance have been increasingly studied in recent years. Therefore, the aim of the present study was to evaluate the effects of an intervention programme aimed at improving the attentional focus of football players, using game situations similar to competitive ones. The participants were 46 male football players belonging to the youth academy of a first division Argentine football club, who were divided into an experimental group and a control group. The methodological design was quasi-experimental, with pre-intervention, post-intervention, and follow-up measures. The measures used were the Psychological Inventory of Sport Performance was used. The results showed significant differences in the variable attentional control in favour of the experimental group compared with the control group after the intervention period and during the follow-up period. On the other hand, the other of the variables analysed (negative coping control, visual image control, positive coping control, and attitudinal control) did not show significant differences between the two groups, but there was a positive trend in the experimental group after the intervention. In conclusion, the use of strategies related to attentional focus in habitual tactical and specific football training tasks seems to have a positive effect on attentional control.